2020
DOI: 10.21608/ejss.2020.29343.1355
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different irrigation water levels and bio-minerals fertilization on fruit yield, quality and water productivity of watermelon grown on sandy soil, Egypt.

Abstract: A FIELD experiment was conducted in farmer's field located at Gammsa district, Dakahlya Governorate, Egypt, during two successive winter seasons 2017 and 2018 to determine and evaluate the response of watermelon grown on sandy soil to three irrigation regimes; 100%(I 1), 85%(I 2) and 70%(I 3) of soil field capacity and four applications of bio-mineral fertilizers; F 1 Applying the recommended dose of NPK (100%RNPK), F 2 (85%RNPK + biofertale), F 3 (70%RNPK + rhizobacterien) and F 4 (55% RNPK+ mixture of biofer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…They reported that deficit irrigation for cucumber under greenhouse condition increased fruit yield and productivity of irrigation water. Increasing cucumber fruit yield under I2 treatment may be due to improving the rate of aeration which increase decomposition of soil organic matter and hence increasing availability of nutrients, therefore, forming healthy plants with good vegetative growth (Moursi et al, 2009, Khalifa et al, 2013and Khalifa, 2020 In regards to Bio-chemical fertilization, the results shown in Table (4) indicated that fruit number, fruit weight and fruit yield were highly significant affected by Biochemical fertilizers application in both growing seasons. The highest mean values of fruit number plant -1 were 128.7 and 131.17; fruit weight were 9.73 and 9.98 kg plant -1 and fruit yield were 37348.36 and 38317.16 kg fed -1 for application fertilizer level (F3) in both growing seasons, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that deficit irrigation for cucumber under greenhouse condition increased fruit yield and productivity of irrigation water. Increasing cucumber fruit yield under I2 treatment may be due to improving the rate of aeration which increase decomposition of soil organic matter and hence increasing availability of nutrients, therefore, forming healthy plants with good vegetative growth (Moursi et al, 2009, Khalifa et al, 2013and Khalifa, 2020 In regards to Bio-chemical fertilization, the results shown in Table (4) indicated that fruit number, fruit weight and fruit yield were highly significant affected by Biochemical fertilizers application in both growing seasons. The highest mean values of fruit number plant -1 were 128.7 and 131.17; fruit weight were 9.73 and 9.98 kg plant -1 and fruit yield were 37348.36 and 38317.16 kg fed -1 for application fertilizer level (F3) in both growing seasons, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it has been demonstrated that biological fertilizers are particularly important as a suitable alternative to mineral fertilizers by enhancing soil fertility, meeting plant nutrition needs and increasing crop yield. (Poraas EL-Din et al, 2008, Khalifa et al, 2013, Saeed et al, 2015and Khalifa, 2020. Under limitation of water resources, high prices of mineral fertilizers and fatal environmental pollution a big problem faces the Egyptian Agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…(2008), Yasari etal. (2008, Megawer and Mahfouz (2010), Mahboobeh and Jahanfur (2012), Morteza and Javad (2013), Sharifi et al (2011), Xiao-bo et al, (2017), and Khalifa (2020. Contribution of groundwater to Etc-canola crop (GWC) Table 7 data indicate that as cut-off irrigation at 85% treatment and alternative irrigation rose during both growing seasons, the groundwater table's contribution to canola water requirements increased.…”
Section: Canola Yield and Its Componentsmentioning
confidence: 99%
“…Water productivity was calculated according to Talha and Aziz (1979) as follows: WP = grains yield (kg ha -1 ) / water applied (m 3 ha -1 ).…”
Section: Water Productivity (Wp)mentioning
confidence: 99%